Isaiah's servants in early Judaism and Christianity: the Isaian servant and the exegetical formation of community identity - Lyons, Michael A.; Stromberg, Jacob (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2021)
"The Book of Isaiah describes an Israelite group called the 'servants, ' who suffered for their righteousness and were promised vindication. This collection of essays shows how the Isaian 'servants' texts were used by early Jewish and Christian readers to shape their own community identity. It includes analyses of Psalms 22, 69, and 102, Daniel, Wisdom of Solomon, Mark, Luke and Acts, Romans, 2 Corinthians, Philippians, 1 Peter, Revelation, and Targum Jonathan on Isaiah, as well as investigations into the relationship between exegesis and identity formation and into how the Isaian Servant(s) are presented within the framework of Israel's history."